The Influence of Leisure Attitudes and Leisure Satisfaction on Adolescents’ Positive Functioning: The Role of Emotion Regulation - Freire, Teresa; Teixeira, Ana (Frontiers in Psychology, 2018)
The abstract was changed and it is included in the revised manuscript